Neurotoxicity among pesticide applicators exposed to organophosphates. Issue 10 (October 1995) - Stokes, L; Stark, A; Marshall, E; Narang, A
Abstract : OBJECTIVES–An epidemiological study of 90 male pesticide applicators licensed in New York was conducted to investigate the effect of exposure to organophosphate pesticides on the peripheral nervous system. METHODS–A cohort of farmers and pesticide applicators from New York State were questioned off season (November 1988-February 1989) and again during the spraying season (April 1989-August 1989) about the presence of several acute signs and symptoms. Short term exposure was validated by measuring the concentration of dimethylthiophosphate (DMTP), a metabolite of guthion, in urine. Chronic signs of subtle peripheral nerve damage were determined by vibration threshold sensitivity of the farmers and applicators tested during November 1988-February 1989 and compared with controls drawn from the general population who were tested during the same time period the next year (November 1989-February 1990). Vibration threshold sensitivity was determined for both the hands and feet. Long term exposure to pesticides was determined by questionnaire. RESULTS–Paired t tests show that mean vibration threshold scores were significantly higher for the dominant (P < 0.00) and non-dominant (P < 0.04) hands among pesticide applicators when compared with scores for population based controls individually matched on age, sex, and county of residence. CONCLUSIONS–A significant increase in mean vibration threshold sensitivity for the dominant and non-dominant hand suggests previous organophosphate exposure among pesticide applicators was associated with a loss of peripheral nerve function.